Deregulation Policy of Tertiary Education and Effects on Human Resources Development in Nigeria - Oluwatosin, W. L.; Bello, S. A.; Ogundele, K. O. (NIU Journal of Humanities, 2020)
Due to studentsâ€™ enrolment explosion in Nigerian universities annually, it becomes imperative that to satisfy the ever-increasing demand for university education, the deregulation of the sector is paramount. This study focused on the implications of the deregulation policy on human resources development. Descriptive research design of survey type was employed for data collection. The sample for the study comprised 100 employers of human resources and 100 parents and lecturers drawn from Lagos and Ogun States because of their representative nature in terms of education and pool of human resources. Stratified random sampling technique was used to obtain the sample. The instrument titled: Implications of Deregulation on Human Resources Development (IDHRD) with 0.85 reliability coefficient was used to collect necessary data from the respondents. The data were analysed using descriptive and inferential statistics. The study revealed that; the deregulation of education influences human resources development in Nigeria; human resources produced from the private higher institutions in Nigeria are not more competent than the human resources from the public higher institutions; the deregulation policy is, to some extent, achieving its goals.  It was concluded that the involvement of major Nigerian stakeholders, complemented by multiple partnerships with international agencies, NGOs, foundations, will be essential if the goals and potential of Nigerian educational system are to be realized. Keywords : Deregulation, Human Resources, Human Resources Development, Capital Goods, and Consumer Goods.